Determination of medicinal compounds in Persicaria odorata using solvent extraction: article / Radiatul Shahila Muhamad Shahrel Hizad, Dr. Norhuda Ismail - Muhamad Shahrel Hizad, Radiatul Shahila; Ismail, Norhuda (2018)
In recent years, the use of herb for medicinal purposes has slowly been accepted into modern treatment. Various studies proved that herbaceous plant contains medicinal compounds that can be used in treatment regime. Persicaria odorata is a plant that grows natively in the South-East Asia. The plant is widely used in Malaysian cuisine and was believed to possess healing power. Although the locals believe that P.odorata leaves can benefit human in various ways, there was scarcity of information regarding the compounds present in the leaves that support the claim as it being a powerful healing agent. In this study, essential oil was extracted from P. odorata leaves by three solvents (hexane, acetone and ethanol). Soxhlet extractor was used as a method of extraction. The extract obtained was then analysed using GC-MS and FTIR to determine the presence of medicinal compounds in the oil. The result shows that extraction using hexane as solvent produced the highest yield of extract. However, acetone is able extract the most bioactive compounds from the dried plant sample (13 compounds) compared to other solvents. GC-MS analysis identified the presence of curlone (11.074%), turmerone (9.94%), squalene (9.94%) and limonene oxide (3.52%) as the major bioactive compounds in the oil. The results of FTIR analysis confirmed the presence of alcohols, phenols, aldehydes, nitro compounds and cellulose. These compounds can benefit human health due to their antioxidant, anticancer, antimicrobial and anti-inflammatory properties. They have great potential to provide alternatives to conventional drugs since the bioactivity of the of the compounds of were proven in various research.